Kreftkoordinatorers rolle i samhandlingsarbeidet i kreftomsorgen i norske kommuner - Syse, Astri; Moshina, Nataliia (Nordisk tidsskrift for helseforskning, 2015)
The role of cancer coordinators in cancer care collaboration in Norwegian municipalities Uncoordinated services represent a pronounced challenge in Norwegian health care. To enhance local cancer care, a trial project implementing cancer coordinator positions in several Norwegian municipalities was launched in 2012. We aim to assess the role cancer coordinators play in the local coordination of cancer care. In 2014, 52% of cancer coordinators in Norwegian municipalities answered a quantitative web survey concerning their role. Cancer coordinators work directly with patients and their families, but are also a resource for other service providers. Collaboration with involved parties is generally adequate, although interactions with general practitioners, NAV, schools and kindergartens could be improved. Cancer prevalence will increase due to population aging, and thus pressure municipal health services. Cancer coordinators report that they contribute positively in local cancer care. Future research should include perspectives also from patients, next-of-kin and collaborating partners, and potential differences in municipalities with and without cancer coordinators should be explored.